A Comment on Servaas Storm's "The New Normal". Issue 4 (2nd October 2017) - Galbraith, James K.
Abstract: Accepting Professor Storm's demolition of total factor productivity growth and production function-based reasoning, this article argues that to understand the great financial crisis and its aftermath requires an evolutionary perspective that goes beyond hysteresis and secular stagnation, that escapes the reification of potential output, and that recognizes how structural forces and not merely deficient demand have affected actual economic growth. It also requires a commonsense understanding of actual American social conditions—no, the middle class has not vanished—and an appreciation that raising living standards under present conditions requires social balance—a new emphasis on collective economic security and public consumption goods.